Experiences With General Education: How Sense of Community Shapes Students' Perceptions. (October 2021) - Cope, Michael R.; Muirbrook, Kayci M.; Jackson, Jorden E.; Park, Paige N.; Ward, Carol; Child, Curtis; Jarvis, Jonathan A.
General education (GE) classes are designed to reflect the mission and goals of the university and to help students become more well-rounded, career-ready, and civically-minded post-graduation. Students' perceptions of these courses have a significant influence on their capacity to succeed, and ultimately to get the most out of their college experience. Using results from an email questionnaire sent to students at a private university in the western United States, we analyze the relationships between perceptions of the GE experience, sense of community, and academic year, and we find that sense of community is positively associated with perceptions of GEs. These results also show freshmen having a higher sense of community than juniors or seniors, and that scholastic class in school is negatively associated with satisfaction with GEs. Furthermore, we find that seniors generally have a lower perception of the importance of GEs in their lives when compared to freshmen.